OP73 The impact of chronic hypertension on adverse maternal and perinatal outcomes: a systematic review and meta-analysis. (3rd September 2019) - Al Khalaf, SY; Barrett, P; McCarthy, FP; O'Reilly, ÉJ; Khashan, AS
Abstract : Background: Chronic hypertension affects up to 5% of all pregnancies, and this is expected to rise due to increasing prevalence of maternal obesity. This study aimed to systematically review observational studies to investigate the risk of adverse perinatal outcomes among pregnant women with chronic hypertension compared with normotensive women. Methods: Medline/PubMed, EMBASE, and Web of Science were searched (from first publication until 10th January 2019) to identify peer-reviewed articles without restriction on language or study period. We included observational studies based on the following criteria: 1) participants were pregnant women; 2) exposure was chronic hypertension; 3) comparison was normotensive women; 4) outcomes included measures of at least one of the following: superimposed pre-eclampsia, small for gestational age, stillbirth, preterm birth, caesarean section, neonatal intensive care unit admission, low birth weight, post-partum hemorrhage maternal death and neonatal death. This review is registered in PROSPERO (CRD42019120088). Two investigators independently reviewed the eligibility criteria, extracted the data and assessed the quality of included studies using the Newcastle-Ottawa tool. A meta-analysis was performed using RevMan 5.3 for each exposure-outcome association, when data allowed. Random effect models were applied for pooling crude and adjusted odds ratios (ORs) respectively. Heterogeneity among studies was assessed using a Cochrane Q statistic and the Higgins I 2 test. Sensitivity analysis was performed by study design, study location, decade of publication, and according to study quality. Publication bias was assessed using Begg's funnel plot and Egger's test. The effect of using antihypertensive medications on the risk of adverse maternal and perinatal outcomes will also be analysed as part of this review. Results: Of the 9739 articles identified, 69 studies met the inclusion criteria. Thirteen studies reported adjusted estimates for small for gestational age (including 7, 070, 558 participants); adjusted pooled OR=1.97 (95% CI, 1.46, 2.67) among women with chronic hypertension compared to normotensive. Similarly, eleven studies reported adjusted estimates for stillbirth (including 15, 231, 939 participants), with a pooled adjusted OR=2.36 (95%CI, 2.18, 2.55). Four studies reported adjusted estimates for neonatal death, the adjusted pooled OR=2.29 (95%CI, 2.03, 2.60). The analyses of other outcomes are ongoing. Conclusion: There are strong associations between chronic hypertension and adverse perinatal outcomes, including small for gestational age, stillbirth and neonatal death. Most studies in this review did not take severity of hypertension into account when comparing the outcomes. This review summarises current knowledge on the association between chronic hypertension and adverse perinatal outcomes and may be used to optimise antenatal care and pregnancy outcomes.